Roadmap for Enterprise Information Management: Strategies and Approaches in 2019 (International Journal of Engineering and Computer Science, 2019)
Purpose: This ongoing research explores the strategy and frameworks employed by key organizations and provides a current roadmap for enterprise information management technologies in today's digital workplace. Theoretical basis: Content and context are examined against published research, new case studies, and actual implementations. Methodology: Research includes ongoing personal correspondence, analysis of existing documents, case studies, and application of these technologies and frameworks during advanced graduate and professional seminars. This research project will combine the results of ongoing research on information management strategies and approaches observed throughout 2019. It suggests that these observations will become trends for the upcoming year. Results: Key stakeholders address the strategic elements of enterprise information management to demonstrate the contemporary importance and reliance for today's organization. Strategies should encompass and harmonize people, processes, data, and technology to address and resolve the global demands and cultural challenges of anyone involved in data capture, creation, information sharing, or analysis. Implications: Technical approaches rigorously aligned with the success of the business will include the people involved. They need to be rewarded for accurate and appropriate data entry, not punished. Analysis of the results is necessary to tweak the processes. Accordingly, adjusting the organizational structures addressing the business benefits of their data will drive long-term success.